Grounds for using fenestration osteotomy at early stages of aseptic necrosis of the femur in adults - Olinichenko, Gennadiy; Filipenko, Volodymyr; Miteleva, Zoya; Poletaeva, Nataliya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article contains materials of experimental studies (measuring of intraosseous pressure, experiments on anatomical preparations, calculation by the finite element method), whose results made it possible to objectively ground performance of a new operation in conditions of aseptic necrosis of the femoral head. These studies made it possible to use the operation at the Institute clinic and therefore are of great theoretical and practical importance.